FemTech concerns: a fundamental rights perspective through the ECHR - Su, Ruoxin (Human rights review, 2025)
Women-specific health issues hold direct relevance for nearly half the global population and are crucial in promoting gender equality. In response, female-oriented technologies (FemTech), digital services and products tailored to women’s physiological features and driven by user-entered data, have gradually emerged, promising to empower female users by enhancing their control and decision-making over their bodies. This promise, however, faces increasing legal and ethical concerns, including privacy intrusion, health risks, digital surveillance, impediments to women’s reproductive freedom, and reinforcement of dominant societal inequalities. Through the lens of the European Convention of Human Rights (ECHR) and its case law, this paper provides a critical examination of how FemTech disrupts certain fundamental (sub-)rights, particularly the right to privacy, reproductive rights, and the prohibition of discrimination. Finally, the analysis acknowledges the inherent insufficiencies of this rights-based approach, assessing how the Convention’s doctrines and state-centric model are challenged by FemTech’s novel integration of digital technologies and women’s unique healthcare demands.